A Retrospective Review of the Outcomes of Migraine Surgery in the Adolescent Population. Issue 6 (June 2015) - Guyuron, Bahman; Lineberry, Kyle; Nahabet, Edward H.
Abstract : Background: Migraine surgery has been studied extensively in adult patients with refractory headaches. The purpose of this study was to review a single surgeon's outcomes following migraine surgery in an adolescent population. Methods: A retrospective review of all patients operated on by the senior author (B.G.) from 2000 to 2014 was performed. All patients aged 18 years or younger with at least 1 year of follow-up after surgery were included. Preoperative and postoperative migraine frequency, duration, severity, and migraine headache days and migraine index were analyzed for statistical significance. Results: A total of 14 patients and 15 operations were analyzed. After an average follow-up of 38.2 months, the frequency of migraine headaches per 30-day period was reduced from 25 to 5 ( p < 0.0001), the migraine headache index decreased from 148.1 to 12.4 ( p < 0.0001), the duration of headaches (number of hours per 24 hours) declined from 0.71 to 0.25 ( p = 0.002), severity of headaches diminished from 8.2 to 4.3 ( p = 0.0004), and migraine days per month declined from 25 to 5 ( p < 0.0001). Five patients remained free of any symptoms following surgery. One patient had no improvement in frequency of headaches, but did have improvement in severity and duration of headaches. No postoperative complications were noted in this group of patients. Conclusion: In the adolescent population with migraine headaches refractory to traditional medical management, migraine surgery may offer symptomatic improvement of migraine headache frequency, duration, and severity in patients with identifiable anatomical trigger sites. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.